LOW-TEMPERATURE THERMODYNAMIC MODEL FOR THE SYSTEM NA2CO3-MGCO3-CACO3-H2O - THE SOLUBILITY OF A NON-IDEAL GAS - Konigsberger E.; Konigsberger L.C.; Gamsjager H. (My University, 1999)
A comprehensive low-temperature thermodynamic model for the geochemically important Na2CO3-MgCO3-CaCO3-H2O system is presented. The model is based on calorimetrically determined ΔfH°298 values, S°298 values and C°p(T) functions taken from the literature as well as on μ°298 values of solids derived in this work from solubility measurements obtained in our laboratories or by others. When these thermodynamic quantities were combined with temperature-dependent Pitzer parameters taken from the literature, solubilities calculated for a wide range of conditions agree well with experimental data. The results for several subsystems were summarized by depicting the respective phase diagrams. For the MgO-CO2-H2O subsystem, it was found that the commonly believed stability relations must be revised, i.e., in the temperature range covered, nesquehonite never becomes more stable than hydromagnesite at pCO2 =< 1 atm. Although the recommended set of thermodynamic data on sparingly soluble solids was derived from experimental results on mainly NaClO4 systems, it can be incorporated in databanks containing additional Pitzer parameters for modeling more complex fresh- or seawater systems.